The Marketing Management of BAZNAS Subang to Increase Muzakki - Purwanti, Neli; Auliya Romdoni, Indi; Hamid, Abdul; Siti Robi'atul Adawiyah, Isna (International Journal of Sharia Business Management, 2024)
Zakat is one part of the pillars of Islam, which is one of the pillars in building the people's economy. Thus, one of the alternative pillars in solving the problem of getting out of poverty is through optimizing the management of zakat funds that are trustworthy and comprehensive as a form of community funds for the benefit and benefit of mankind. The Amil Zakat Agency formed by the government aims to manage Zakat, infaq, shadaqah. The management of zakat is not solely carried out individually, from muzakki it is handed over directly to mustahiq, but is carried out by an institution that specifically handles zakat, infaq and shadaqah. With the various obstacles faced by the Subang Regency National Amil Zakat Agency, it is necessary to have a management for marketing, because if the marketing is not good, then everything will not run smoothly and will not be able to increase the number of muzakki. This research is a case study research using a qualitative approach by collecting data through observation, interviews and documentation. Data analysis used with data reduction, data presentation and verification. In this study a conclusion can be drawn that the implementation of marketing management carried out by BAZNAS Subang Regency has not fully run in accordance with the provisions that have been implemented.